The glycerol stabilized calcium phosphate cluster for rapid remineralization of tooth enamel by a water-triggered transformation - Nan Luo; Bing-Qiang Lu; Yu-Wei Deng; Hua Zeng; Yu Zhang; Jing-Yu Zhan; Xiao-Chen Xu; Gui-Zhi Cao; Jin Wen; Zhiyuan Zhang; Xi-Ping Feng; Xinquan Jiang; et al. (Nature Communications)
Abstract Remineralization is a common strategy for the repair of early demineralized tooth enamels, but the harsh dynamic oral environment often hampers its efficacy. Rapid remineralization is expected to address this challenge, however, the stabilizers of remineralization materials often resist their transformation required for repair. Here, by dissolving the ions of calcium and phosphate in glycerol-dominant solvents, we obtain the calcium phosphate clusters (1–2 nm), which are stabilized by glycerol (with high viscosity and affinity to clusters), but can perform a fast enamel repair via the water-triggered transformation in both static and dynamic environments. Upon the in vitro and in vivo (female Sprague-Dawley rats) studies, the clusters swiftly enter the nano-/micro-sized enamel defect sites, then form a compact hydroxyapatite repair layer within a short time (30 min, much faster than the conventional materials), and significantly recovers mechanical properties. This material is promising for large-scale preparation and applications in dental remineralization.